Proximate Analysis and Estimation of Total Phenolics, Flavonoids, Ascorbic Acid in Methanolic Extracts of Plant Seeds - Thymus Vulgaris, Salvia Hispanica, Nigella Sativa, Anethum Graveolens - Bagyalakshmi N., Narayanan; Kannasandra Ramaiah, Manjula; G. Singh, Kavitha (Journal of Neonatal Surgery, 2025)
Plant kingdom offers many herbs that are rich in micronutrients and secondary metabolites which have the potential to improve health by preventing and treating illnesses. These nutrients when consumed in the right amounts, helps to postpone aging and increase longevity. A large number of them are sold as dietary supplements. They are becoming more and more popular these days because of their nutritional worth as well as their medicinal purposes. Ginseng, Echinacea, green tea, glucosamine, omega 3, lutein, folic acid, and cod liver oil are a few well-known nutraceuticals. The usage of edible seeds and their oil has grown in popularity because they are rich in dietary fiber, proteins, vitamins, minerals, vital fatty acids, antioxidants, phenolic compounds, secondary metabolites, and carbs. In the present study four seeds namely Thymus vulgaris, Salvia hispanica, Nigella sativa, Anethum graveolens are analyzed for their phytochemicals and their nutrient content are estimated by standard methods. The results revealed that the selected seeds possess significant amount of crude fibers, proteins and secondary metabolites and thus can be used as functional foods to improve general health.